PENGARUH PEMEBERIAN CMA TERHADAP PERTUMBUHAN AKAR TANAMAN KACANG KORO PEDANG (Canavalia ensiformis L.) - Sari, Dwi Nur Rikhma (Pendidikan Biologi,Universitas Islam Jember, 2012)
The purpose of this research was to know the effect of CMA with different concentrations (0, 10, 20, 30 g) on roots growth of Jackbean plants (Canavalia ensiformis) consisting of root biomass and root length. This research is an experimental design wich is used Completely Randomized Design (CRD). The treatment in this experiment was inoculating the CMA in various concentrations to the rhizosphere of the soil which would be used as the medium for the C. ensiformis growth. Data were analyzed using ANOVA and followed by Duncan's test 5%. Results of this research indicated that no a marked different for of root biomass and root length, however giving of CMA at a concentration of 30 g showed best value for the parameters of root biomass (37,84 g) and root length (55,24 g).Keywords: Canavalia ensiformis, CMA, Roots